Emotional Awareness In Syiah Kuala University Students - Asfaruddin, Khairiah; Nurhasanah, Nurhasanah; Wildania, Wildania (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2025)
Emotional awareness in early adulthood, especially among college students, is a critical component of psychosocial development that can affect academic success and adjustment in the campus environment. This study aims to determine the level of emotional awareness among students at Syiah Kuala University. This research employs a quantitative approach with a descriptive research design. The population in this study consisted of all students at Syiah Kuala University, totaling 28,004 students. The sample size was 398 students, determined using a simple random sampling technique, with the number of samples calculated through the Slovin formula at a 5% error rate. Data were collected using the Emotional Awareness Questionnaire (EAQ30), which consists of 30 statement items. The collected data were then analyzed using the percentage formula. Based on the results of the descriptive analysis, it was found that most students (62%) have a level of emotional awareness in the moderate category, while 31% of students fall into the high category, 4% into the low category, and 2% into the very high category. Analysis by aspect shows that the â€œAnalysis of Emotionsâ€ has the highest value (48%), indicating students’ ability to analyze and understand the causes of their emotions. This is followed by â€œAttending to Others’ Emotionsâ€ (39%), which reflects the ability to empathize and understand the emotions of others, and â€œDifferentiating Emotionsâ€ (32%), demonstrating a good ability to distinguish between emotions. In conclusion, on average, Syiah Kuala University students exhibit good emotional awareness, indicating a positive potential for facing emotional challenges.